Kruppel-Like Factor 4 Positively Regulates Autoimmune Arthritis in Mouse Models and Rheumatoid Arthritis in Patients via Modulating Cell Survival and Inflammation Factors of Fibroblast-Like Synoviocyte - Choi, Seungjin; Lee, Kijun; Jung, Hyerin; Park, Narae; Kang, Jaewoo; Nam, Ki-Hoan; Kim, Eun-Kyeong; Ju, Ji Hyeon; Kang, Kwi Young (Frontiers in Immunology, 2018)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes mild to severe joint inflammation. During RA pathogenesis, fibroblast-like synoviocytes (FLS) acquire a tumor-like phenotype and mediate cartilage destruction both directly and indirectly by producing proinflammatory cytokines and matrix metalloproteinases (MMPs). KLF4, a member of the KLF family, plays significant roles in cell survival, proliferation, and differentiation. A recent study reported increased expression of KLF4 in synovial tissue from RA patients. However, its precise role in rheumatoid arthritis in different models, including mouse autoimmune disease models, remains unclear. In this study, we examined the role of KLF4 during development of autoimmune arthritis in mouse models. To do this, we used KLF4 knockout mice rendered by Ribonucleic acid (RNA)-guided endonuclease (RGEN) and performed collagen antibody-induced arthritis (CAIA). We found that deletion of KLF4 reduces inflammation induced by CAIA. In addition, we assessed collagen-induced arthritis (CIA) in control mice and KLF4-overexpressing mice generated by a minicircle vector treatment. Severity of CIA in mice overexpressing KLF4 was greater than that in mice injected with control vector. Finally, we verified inflammatory roles of KLF4 in CIA by treating Kenpaullone used as KLF4 inhibitor. Next, we focused on human/mouse FLS to discover the cellular process involved in RA pathogenesis including proliferation, apoptosis and inflammation including MMPs. In FLS, KLF4 upregulated expression of mRNA encoding proinflammatory cytokines IL-1β and IL-6. KLF4 also regulated expression of MMP13 in the synovium. We found that blockade of KLF4 in FLS increased apoptosis and suppressed proliferation followed by downregulation of anti-apoptotic factor BCL2. Our results indicate that KLF4 plays a crucial role in pathogenesis of inflammatory arthritis in vivo, by regulating apoptosis, MMP expression, and cytokine expression by FLS. Thus, KLF4 might be a novel transcription factor for generating RA by modulating cellular process of FLS.